1998
DOI: 10.1161/01.cir.97.23.2316
|View full text |Cite
|
Sign up to set email alerts
|

Myocyte Recovery After Mechanical Circulatory Support in Humans With End-Stage Heart Failure

Abstract: Background-The failing myocardium is characterized by decreased force production, slowed relaxation, and depressed responses to ␤-adrenergic stimulation. In some heart failure patients, heart function is so poor that a left ventricular assist device (LVAD) is inserted as a bridge to transplantation. In the present research, we investigated whether circulatory support with an LVAD influenced the functional properties of myocytes from the failing heart. Methods and Results-Myocytes were isolated from human expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
221
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(233 citation statements)
references
References 43 publications
10
221
0
2
Order By: Relevance
“…Studies in end-stage heart failure patients treated with left ventricular assist devices have shown that mechanical unloading improves myocyte function and reverses structural remodeling of the failing heart (35,36). This therapy also normalizes Ca 2ϩ transients and increases SERCAmediated Ca 2ϩ uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in end-stage heart failure patients treated with left ventricular assist devices have shown that mechanical unloading improves myocyte function and reverses structural remodeling of the failing heart (35,36). This therapy also normalizes Ca 2ϩ transients and increases SERCAmediated Ca 2ϩ uptake.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies in end-stage heart failure patients treated with left ventricular assist devices have shown that mechanical unloading improves myocyte function and reverses structural remodeling of the failing heart (7,8). This therapy also normalizes Ca 2ϩ transients and increases SERCA-mediated Ca 2ϩ uptake.…”
Section: Table 1 Hemodynamic Measurements In Ql and Wt Micementioning
confidence: 99%
“…Furthermore, many cellular processes improve, although they do not completely normalise. [5][6][7][8][9][10][11][12][13][14][15] Sufficient recovery of left ventricular function, allowing LVAD explantation, however, is rare and is mainly feasible in patients suffering from acute myocarditis or PPCM. 10,11,13 In these cases, the LVAD will maintain the patient's life, allowing the myocardium to recover from the underlying disease.…”
Section: Discussionmentioning
confidence: 99%